Design, biological activity and signaling pathway of bovine consensus omega interferon expressed in Pichia pastoris. (February 2019) - Gao, Mingchun; Guo, Yongli; Luo, Xiuxin; Du, Jiwen; Wang, Yujiao; Cao, Chong; Wang, Junwei; Han, Wenyu
Highlights: CoBoIFN-ω is the first artificial consensus IFN-ω. CoBoIFN-ω codon-optimized was successfully expressed in Pichia pastoris . CoBoIFN-ω has better biological characteristics than the naturally occurring BoIFN-ω. CoBoIFN-ω exerts antiviral activity through JAK-STAT signaling pathway. Abstract: The bovine IFN-ω (BoIFN-ω) multigene family is located on chromosome 8, which has 14 potential functional genes and 10 pseudogenes. After aligning 14 BoIFN-ω subtypes and assigning the most frequently occurring amino acids in each position, one artificial consensus BoIFN-ω (CoBoIFN-ω) gene was designed, optimized and synthesized. Then, CoBoIFN-ω was expressed in Pichia pastoris, which was demonstrated to have 3.94-fold and 14.3-fold higher antiviral activity against VSV on MDBK cells than that of BoIFN-ω24 and BoIFN-ω3, respectively. Besides this, CoBoIFN-ω was confirmed to have antiviral activity against VSV on BL, BT, PK-15 cells, and against BEV, BHV-1, BPIV3 on MDBK cells. Additionally, CoBoIFN-ω could bind with bovine type I IFN receptors, and then activate the promoters of NF-κB, ISRE and BoIFN-β, and induce the transcription of ISGs and expression of Mx1 and NF-κB p65, which suggested CoBoIFN-ω exerts antiviral activity via activation of the JAK-STAT signaling pathway. Overall, this research on CoBoIFN-ω not only extends and improves consensus IFN research, but also reveals that CoBoIFN-ω has the potential to be used in the therapy of bovine viral diseases.